1992
DOI: 10.1002/ar.1092330312
|View full text |Cite
|
Sign up to set email alerts
|

Development of the human sphenomandibular ligament

Abstract: The development and arrangement of the sphenomandibular ligament of 60 human embryos and fetuses were studied. Meckel's cartilage appeared as a single, continuous fibrous structure lying between the mandibular lingula and the malleus of the middle ear in fetuses of 210 mm crown-rump length (22 weeks of age) and over. This structure constitutes the malleolomandibular ligament, and two clearly differentiated portions bound by the tympanosquamosal fissure could be seen: a juxtaarticular portion, inserted on the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(10 citation statements)
references
References 7 publications
1
8
0
1
Order By: Relevance
“…134,135,136,137,138,139,140141,142,143,144 DML and AML are responsible for such bone communication and connection; they are attached to the oscicular chain (malleus) and may create a biomechanical connection between the middle ear and the mandible. 145,146,147,148 These findings is corroborated in 23 human temporal bone specimens ( Figure 13) that consistently show these ligamental structures. 149 These ligamental structures may be stretched by a TMJ disorder, which could affect middle ear oscicular equilibrium; although, there is controversy about their ability to disturb the oscicular chain.…”
Section: First Bone Common Passages Explorationsupporting
confidence: 63%
See 1 more Smart Citation
“…134,135,136,137,138,139,140141,142,143,144 DML and AML are responsible for such bone communication and connection; they are attached to the oscicular chain (malleus) and may create a biomechanical connection between the middle ear and the mandible. 145,146,147,148 These findings is corroborated in 23 human temporal bone specimens ( Figure 13) that consistently show these ligamental structures. 149 These ligamental structures may be stretched by a TMJ disorder, which could affect middle ear oscicular equilibrium; although, there is controversy about their ability to disturb the oscicular chain.…”
Section: First Bone Common Passages Explorationsupporting
confidence: 63%
“…149 These ligamental structures may be stretched by a TMJ disorder, which could affect middle ear oscicular equilibrium; although, there is controversy about their ability to disturb the oscicular chain. 150,151,152,153 The spread of forces through cranial bone sutures was treated by Libin in 1987 and suggested that ligaments common to neighbouring structures could become tensioned during normal physiological mobilization and in abnormal temporal bone trauma. 154 Retrodiscal tissue elasticity can normally act as an energy buffer in spreading movement from the TMJ to the middle ear by such common ligaments; however, TMJ disc luxation or oedematous pressure from an inflammatory disorder could certainly cause tension on the malleus through Huguier's canal.…”
Section: First Bone Common Passages Explorationmentioning
confidence: 99%
“…[11][12][13][14] However, few reports 15 described the attaching style of the sphenomandibular ligament to the mandible. Therefore, in this study, the sphenomandibular ligament and its attaching style to the mandible was observed.…”
mentioning
confidence: 99%
“…In fetal heads, Meckel's and Reichert's cartilages show a significant change in morphology as the final derivatives form [22-25]. Calcification can occur in either of these cartilages at specific sites such as the ear ossicles and styloid process.…”
Section: Discussionmentioning
confidence: 99%